Sparstolonin B Exerts Therapeutic Effects on Collagen-Induced Arthritis by Inhibiting the NLRP3 Inflammasome and Reducing the Activity of α1,3-Fucosyltransferase - Yue Sun; Yun Guo; Jing Zhang; Lihua Chang; Haiyan Zhao; Xiaofei Wang (Mediators of Inflammation)
Objective. To explore the role of α1,3-fucosyltransferase in the mediation of rheumatoid arthritic inflammation, the protective effect of Sparstolonin B on rheumatoid arthritis (RA), and the mechanisms that regulate the NLRP3 inflammasome. Methods. Forty, weighing from 260-300 g, male Sprague-Dawley rats were randomly divided into the following groups: a sham operation group (Sham group), a rheumatoid arthritis model group (RA group), an RA+Sparstolonin B treatment group (RAS group), an RA+Iguratimod group (RAI group), and an RA+SsnB+NLRP3 inflammasome activator (Nigericin) group (RASN group); ten animals were allocated to each group. We determined the arthritis index for each group of rats, and pathological changes were evaluated by hematoxylin-eosin staining. We also used ELISAs to determine the serum levels of IL-17, IL-6, TNF-α, TGF-β, IL-18, and IL-1β. TUNEL staining was used to investigate apoptosis in synovial cells. IF was used to detect the release of ROS, ASC formation, and the expression levels of FucT-V and NLRP3. Western blotting was used to detect the protein expression levels of Bc1-2, Bax, TLR4, MYD88, NF-κB, pro-caspase-1, NLRP3, FucT-V, E-Selectin, and P-Selectin. We also performed in vitro experiments with Sparstolonin B and detected changes in 1,3-fucosyltransferase activity by ELISA. The pyroptosis-related phenotype, including ASC, was identified by immunofluorescence, while levels of NLRP-3, pro-IL-1, and pro-caspase-1 were detected by western blotting. Results. Sparstolonin B was showed to alleviate joint swelling in RA rats, inhibited inflammatory cell infiltration and the release of ROS, reduced damage caused by oxidative stress, and suppressed the rate of apoptosis in synovial cells. The administration of Sparstolonin B inhibited the secretion of IL-17 from Th17 cells and triggered the secretion of TGF-β from Treg cells, thus leading to the reduced expression of TLR4, MyD88, and NF-κB, and the suppression of TNF-α secretion. Moreover, Sparstolonin B downregulated the expression of NLRP3, inhibited ASC formation in vivo and in vitro, and reduced the levels of IL-18 and IL-1β. The expression levels of FucT-V, E-Selectin, and P-Selectin were also inhibited. Interestingly, these protective effects of Sparstolonin B could be blocked in RA rats by inhibiting the activation of the NLRP3 inflammasome. Conclusion. Sparstolonin B improved inflammatory responses and oxidative stress by inhibiting the NLRP3 inflammasome, inhibiting the expression of FucT-V and downregulating the TLR4/MYD88/NF-𝜅B signaling pathway in order to rescue RA.